2015
DOI: 10.15282/jmes.8.2015.24.0146
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Heat Transfer Analysis of Waste Heat Exchanger for Exhaust Gas Energy Recovery

Abstract: Waste heat is heat that is usually thrown into the environment even though it could still be reused for some useful and economic purpose. For example, any exhaust gas stream with a temperature of above 80°C has the potential for significant waste heat recovery. Therefore, an attempt to reuse the exhaust waste energy to transfer the energy to any energy cycle is a worthwhile effort. In the present study, the waste energy from the exhaust gas of an internal combustion engine is recovered by converting it to ammo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The high performance of plant can be judged by its power generation, fuel consumption, working ratio and the thermal efficiency [1][2][3][4]. It is reported that various aspects are there which greatly influence the performance which is: surrounding temperature, pressure ratio, combustion and the turbine inlet temperatures, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The high performance of plant can be judged by its power generation, fuel consumption, working ratio and the thermal efficiency [1][2][3][4]. It is reported that various aspects are there which greatly influence the performance which is: surrounding temperature, pressure ratio, combustion and the turbine inlet temperatures, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, a large number of studies dealing with the effects of the Dufour and Soret parameters on heat and mass transfer problems on Newtonian and viscoelastic fluids have appeared [12,13]. These effects are considered as second order phenomena and have often been neglected in the heat and mass transfer processes [14][15][16]. Bég et al [17] emphasised the effect of Soret and Dufour on convective heat and mass transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, R22 is used as a refrigerant in most air conditioning systems for its suitable properties such as stability, non-toxicity, non-flammability [1][2][3][4] and good thermodynamic properties [5]. The general cause of ozone layer depletion is that Chlorofluorocarbons (CFCs) and Hydrochlorofluorocarbons (HCFCs) which are a large class of chlorine containing chemicals, migrate to the stratosphere where they react with the ozone [6].…”
Section: Introductionmentioning
confidence: 99%